Estratégias para captação de investimentos de risco por healthtechs brasileiras à luz da teoria causation-effectuation - Silva, Maria Andresa Santana (2023)
The Covid-19 pandemic made the inequalities in the healthcare sector explicit in the world, a decisive factor driving the development of healthtechs. These ventures highlight health as a fundamental bastion, since they bring together technology, data, and medical knowledge to improve people's living conditions. Given this reality and the opportunities arising from the health sector, more than US$ 500 million have been invested nationally in healthtechs, motivating new investors and boosting the economy. In accordance with the above, this research aimed to analyze the strategies used to attract risk investments by Brazilian healthtechs using the causation-effectuation theory. As for the methodological procedures, this study was guided by a qualitative perspective, together with managers of Brazilian healthtechs. The strategy used was the multiple case method. For data collection, the following sources of evidence were used: participant observation at events related to the theme; analysis of documents and national sectorial intelligence reports; semi-structured interviews; and data from the Crunchbase platform. For data treatment and analysis, the technique adopted was content analysis, using the Atlas.ti version 23 and Microsoft Word online version 365 software. As results, it was possible to notice: 1) a 142% increase in the number of healthtechs in the national scope in the last two years, even in the face of the circumstances caused by the pandemic; 2) in terms of investments, approximately 60% of Brazilian healthtechs had already received some kind of investment; 3) during the initial phases of these startups, the commontypes of investments were: equity or bootstrapping, public edicts, venture capital funds and angel investors; 4) of the 34 healthtechs registered on Crunchbase, the healthtech Bloom Care was the company that raised the most investments between the years 2021 and 2022; 5) the causation-effectuation theory has a direct and indirect influence on all phases of healthtech development; and 6) in the initial phases, ideation and traction, entrepreneurs are likely to follow the premises of the effectuation theory; however, in the expansion and maturity phases, entrepreneurs are more likely to follow the assumptions of the causation theory. Therefore, it is concluded that, among the investment attraction strategies mentioned, having a business structure that attracts the attention of the investor, with fair shareholding and mechanisms that ensure the exit of the investment is a considerable factor at the time of the decision to invest in the business.